Keterampilan Belajar vs Belajar Keterampilan - Dwi Nugroho Hidayanto (Universitas Negeri Malang, 2016)
To anticipate global challenge, some Indonesia scholars issued a discourse entitled Life-skilled Based Education. In one hand, it is needed in order to enter global trends and to provide students with any know-how that relevant to districts development program as well as to enrich individual skills needed in daily life. But in other hand, it was a debatable theme because most of scholars still placed skill to learn is more important than learn to have skill that identical to learn for earning. This article elaborates between these two differ perspective